Analysis of flow and heat transfer through a partially blocked fuel subassembly of fast breeder reactor. (January 2020) - Sarkar, Madhusree; Velusamy, K.; Munshi, P.; Singh, Om Pal
Abstract: The influence of local porous flow blockage in the active region of a prototype fuel subassembly having 217 helical wire wrapped pins and five helical pitch length of a sodium cooled fast reactor has been investigated. A non-Darcy porous flow model has been adopted for the investigation. The prediction capability of the model has been validated against the published sodium experiments on a 19-pin electrically heated bundle. The blockage parameters, viz., radius, axial height, porosity and debris size have been systematically varied over a range of practical interest. The critical blockage height that leads to risk of local sodium boiling within blockage (i.e. clad temperature approaching sodium boiling point) has been determined as a function of other parameters. The parametric zone which is safe has been identified from the study. Radial extent of blockage and blockage porosity are found to be the most important parameters that influence the thermal hydraulic characteristics. In the wake region behind the blockage, flow gets established within a short length. However thermal mixing is incomplete. The local porous blockage does not significantly alter the total pressure drop in the bundle region, suggesting bulk temperature rise of sodium in the subassembly will be very marginal, though there can be a risk of local sodium boiling and associated clad failure.